Pengaruh Komunikasi, Komitmen dan Budaya Organisasi Terhadap Kinerja Organisasi : (Studi pada Pegawai Kantor Dinas Perindustrian, Koperasi dan Perdagangan Kota Banjar) - Ago Wijaya; Irma Bastaman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is motivated by the low performance of employees which can be seen from the quality and quantity of work that is still not in accordance with the planning. The low performance of employees is thought to be influenced by ineffective communication, low employee commitment, and organizational culture that is still not conducive. The purpose of this study is to determine how communication affects organizational performance, how commitment affects organizational performance, how organizational culture affects organizational performance, and how communication, commitment and organizational culture together affect organizational performance. The method used in this study uses a quantitative descriptive method. To analyze it, statistical correlation and multiple regression test data analysis was used using SPSS version 22.00. The results of the study obtained provide the conclusion that communication has a positive and significant effect on organizational performance, commitment has a positive effect on organizational performance, organizational culture has a positive effect on organizational performance and communication, commitment and organizational culture together affect organizational performance.